Factores que influyen en el establecimiento y producción de pastizales que limitan el desarrollo ganadero en Ecuador - Cercado Solórzano, Ronald Enrique (2021)
The objective of this research is to determine and describe the factors that influence the establishment and production of pastures causing the limitation of livestock development in Ecuador. The methodology used for the development of the research is the inductive-deductive method, which consists of collecting information from electronic media, text, magazines, among others. Cattle raising is an economic activity in which human, physical and financial resources work together to obtain food products. In order for livestock to have an adequate production rate, they must be provided with feed, with pasture being the main source. Pastures are large extensions covered with vegetation that can be exploited through the use of grazing systems for animal feeding. The production and establishment of pastures depends on different factors which, depending on the management carried out, may define pastures with a high nutritional load or, on the contrary, pastures that do not have sufficient properties to meet the nutritional needs of livestock. The research carried out allowed us to learn about the management factors, production systems, selection of pasture species, economic factors and stocking rates that influence the establishment of pastures. The limited development of Ecuadorian livestock is mainly attributed to the negative influence that arises when these factors are not adequately managed to reduce their incidence.